Karakteristik Kimia dan Sensori Seduhan Serbuk Semanggi (Marsilea crenata) dengan Penambahan Jahe Merah (Zingiber officinale) - Linda Mei Velina; Lia Amalia; Muhammad Fakih Kurniawan (LPPM Universitas Terbuka, 2023)
Clover (Marsilea crenata) has the potential to be used as powder infusion products because its benefits to health. The disadvantage of clover leaf is it produce an unpleasant aroma that requires the addition of spices. This study aims to study the effect of clover powder formulations and red ginger (Zingiber officinale) spice on the chemical and sensory characteristics of herbal infusion. This study used Completely Randomized Design (CRD), namely the comparison of Clover leaf powder and red ginger powder, namely (95%:5%), (90%:10%), (85%:15%) and (80%:20%). The analysis included moisture content, ash content, antioxidant activity, water soluble extract content as well as sensory quality tests and hedonic tests. The data were analyzed statistically using ANOVA and continued with DNMRT at the 5% level. The addition of red ginger powder had a significant effect on moisture content, ash content, antioxidant activity (IC50), water soluble extract content, and descriptive and hedonic sensory assessment and overall assessment. The selected formula based on the final result is the addition of 80% clover powder and 20% red ginger powder with a water content of 16.68%; ash content 4.71%; antioxidant activity 207.745 ppm; and water-soluble essence content of 19.02%. The sensory quality test of the selected products obtained a brownish-green color, not unpleasant, and a bit spicy. The results of the hedonic test showed that the color, aroma, and taste of powder infusion were preferred by the panellists.